(untitled) (Advancements in Homeopathic Research, 2024)
India has an extremely diverse range of plants, many of which have therapeutic applications. The rich resource is being over-exploited and is diminishing at an alarming rate. Therefore, it is crucial to adopt strategies for the sustainable management of resources derived from traditional medicinal plants. The diverse array of secondary metabolites found in plants not only imparts therapeutic effects but also forms the cornerstone of medicinal advancements in pharmaceutical formulations.